The ERK/CREB pathway is involved in the c-Ski expression induced by low TGF-β1 concentrations during primary fibroblast proliferation. Issue 11 (3rd June 2018) - Li, Ping; Liu, Ping; Peng, Yan; Zhang, Zhuo-Hang; Li, Xiao-Ming; Xiong, Ren-Ping; Chen, Xing; Zhao, Yan; Ning, Ya-Lei; Yang, Nan; Zhang, Bo; Zhou, Yuan-Guo
ABSTRACT: Increasing evidence has suggested that bidirectional regulation of cell proliferation is one important effect of TGF-β1 in wound healing. Increased c-Ski expression plays a role in promoting fibroblast proliferation at low TGF-β1 concentrations, but the mechanism by which low TGF-β1 concentrations regulate c-Ski levels remains unclear. In this study, the proliferation of rat primary fibroblasts was assessed with an ELISA BrdU kit. The mRNA and protein expression and phosphorylation levels of corresponding factors were measured by RT-qPCR, immunohistochemistry or Western blotting. We first found that low TGF-β1 concentrations not only promoted c-ski mRNA and protein expression in rat primary fibroblasts but also increased the phosphorylation levels of Extracellular Signal-Regulated Kinases (ERK) and cAMP response element binding (CREB) protein. An ERK kinase (mitogen-activated protein kinase kinase, MEK) inhibitor significantly inhibited ERK1/2 phosphorylation levels, markedly reducing c-Ski expression and CREB phosphorylation levels and abrogating the growth-promoting effect of low TGF-β1 concentrations. At the same time, Smad2/3 phosphorylation levels were not significantly changed. Taken together, these results suggest that the increased cell proliferation induced by low TGF-β1 concentrations mediates c-Ski expression potentially through the ERK/CREB pathway rather than through the classic TGF-β1/Smad pathway.